2014
DOI: 10.1063/1.4869245
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron radiation, pair production, and longitudinal electron motion during 10-100 PW laser solid interactions

Abstract: At laser intensities above 10 23 W/cm 2 the interaction of a laser with a plasma is qualitatively different to the interactions at lower intensities. In this intensity regime solid targets start to become relativistically underdense, gamma-ray production by synchrotron emission starts to become an important feature of the dynamics and, at even higher intensities, electron-positron pair production by the non-linear Breit-Wheeler process starts to occur. Previous work in this intensity regime has considered ion … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 15 publications
(34 reference statements)
5
56
0
Order By: Relevance
“…However, this process is expected to happen on a timescale an order of magnitude longer than those considered. Moreover, in [55], the screening has been and resulting low absorption due to QED effects has been seen in simulations with similar parameters to those explored here. As a test, we have conducted a 2D simulation for initial target and laser parameters in regime III.…”
Section: The Two Regimes Of Ultra-high Intensity Laser-solid Interactsupporting
confidence: 64%
“…However, this process is expected to happen on a timescale an order of magnitude longer than those considered. Moreover, in [55], the screening has been and resulting low absorption due to QED effects has been seen in simulations with similar parameters to those explored here. As a test, we have conducted a 2D simulation for initial target and laser parameters in regime III.…”
Section: The Two Regimes Of Ultra-high Intensity Laser-solid Interactsupporting
confidence: 64%
“…In the QED laser-plasma interaction regime, a promising mechanism for production of γ -ray photons is the nonlinear synchrotron radiation252627282931 of ultrarelativistic electrons in the laser fields, i.e., 30. It is shown that γ -ray photons with the maximum energy extending to 100 s MeV can be generated by irradiating a solid target with an ultraintense laser262728.…”
mentioning
confidence: 99%
“…In the QED laser-plasma interaction regime, a promising mechanism for production of γ -ray photons is the nonlinear synchrotron radiation252627282931 of ultrarelativistic electrons in the laser fields, i.e., 30. It is shown that γ -ray photons with the maximum energy extending to 100 s MeV can be generated by irradiating a solid target with an ultraintense laser262728. However, for laser interaction with steep solid density targets, where no preplasmas exist, the γ -ray emission occurs only in the small skin-depth region2262728, therefore, the conversion efficiency from laser to γ -rays is still low, and the peak brightness of γ -rays is also limited.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have simulated cascades using the particle-in-cell (PIC) code EPOCH, [32], which includes the strong-field QED processes described above [33]. 1D and 2D simulations have been performed in order to show where in I 24 -n 0 space cascades and dense pair plasmas will develop, as has previously been done for gamma-ray emission by nonlinear Compton scattering only [34]. In doing so, we outline expectations for future experiments using ultra-high intensity lasers and provide an approximate model for predicting the production of a dense pair plasma over a wide range of possible experimental conditions.…”
Section: Introductionmentioning
confidence: 99%